Cellular and humoral immunity of virus-induced asthma - Okayama, Yoshimichi (Frontiers in Microbiology, 2013)
Asthma inception is associated with respiratory viral infection, especially infection with respiratory syncytial virus (RSV) and/or human rhinovirus (HRV), in the vast majority of cases. However, the reason why RSV and HRV induce the majority of bronchiolitis cases during early childhood and why only a small percentage of children with RSV- and HRV-induced bronchiolitis later develop asthma remains unclear. A genetic association study has revealed the important interaction between viral illness and genetic variants in patients with asthma. Severe RSV- and HRV-induced bronchiolitis may be associated with a deficiency in the innate immune response to RSV and HRV. RSV and HRV infections in infants with deficient innate immune response and the dysfunction of regulatory T cells are considered to be a risk factor for the development of asthma. Sensitization to aeroallergens, beginning in the first year of life, consistently predisposes children to HRV-induced wheezing illnesses, but the converse is not true. Some evidence of virus specificity exists, in that allergic sensitization specifically increased the risk of wheezing in individuals infected with HRV, but not RSV. Administration of Palivizumab, a humanized monoclonal antibody that targets the A antigenic site of the Fusion-protein of RSV, decreases the risk of hospitalization in high-risk infants and the risk of recurrent of wheezing. However, palivizumab did not have any effect on subsequent recurrent wheezing in children with a family history of atopy. These findings suggest that infection with RSV and infection with HRV might predispose individuals to recurrent wheezing through an atopy-independent and an atopy-dependent mechanism, respectively. Respiratory virus-induced wheezing illnesses may encompass multiple sub-phenotypes that relate to asthma in different ways.